Pelvic organ prolapse: Women's experiences of Accessing Care & Recommendations for improvement - Louise Carroll; Cliona O'. Sullivan; Catherine Doody; Carla Perrotta; Brona M. Fullen (BMC, 2023)
Abstract Up to 50% of women will develop pelvic organ prolapse (POP) over their lifetime. Symptoms include pain, bulge, urinary, bowel and sexual symptoms affecting all aspects of a woman's life. Many women with POP symptoms present initially to primary care settings. Research has shown these interactions are often unsatisfactory, with women reporting their health care professional (HCP) trivialized their symptoms or appeared to have poor knowledge about pelvic floor dysfunction (PFD). Aim The aim of this qualitative study was to explore experiences of younger women seeking treatment for POP and their recommendations for improvements. Methods Ethics approval was obtained (LS-21-01-Carroll-Ful). Women with POP were recruited from an online support group (n = 930 members). Inclusion criteria: adult women, diagnosed with POP and aware of their POP stage. Following informed consent, a demographic questionnaire, interview questions and the Central Sensitization Inventory (CSI) were forwarded. Semi-structured zoom audio-recorded interviews were conducted. Thematic analysis was undertaken; transcripts coded, and themes identified. Results Fourteen women aged 32-41, parity 1-3, with POP Grade 1-3 participated. Many women reported HCPs as dismissive or not appreciative of the impact of their condition. Others described interactions with HCPs who they felt listened, understood the impact of their POP, gave simple explanations, a positive prognosis and outlined a realistic treatment plan. Current antenatal education, post-partum care and primary HCP screening for PFD were identified by women as deficient. Many highlighted delays in accessing specialist care for POP. Women made several recommendations for improvements to the current model of care. Conclusions Increased focus on person-centred care, particularly emotional support, information and education may improve younger women's experiences when seeking care for POP.